Numerical modeling of therapeutic lens drug delivery in the anterior human eye for the treatment of primary open-angle glaucoma. (September 2020) - Bhandari, Ajay; Bansal, Ankit; Sinha, Niraj
A numerical model of drug delivery from a therapeutic lens in the anterior portion of the human eye has been developed for a more effective treatment plan of primary open-angle glaucoma. The numerical model takes into account the drug diffusion through the therapeutic lens along with heat transfer and aqueous humor flow in different orientations of the human eye (supine (two-dimensional) as well as standing (three-dimensional)). Results illustrate that the drug diffuses through the therapeutic lens to the cornea and is convected into the anterior chamber of the eye due to the temperature gradient across the eye. In addition, eye orientation significantly affects drug delivery with supine orientation providing better and uniform drug exposure in different target regions of the eye as compared to standing in the case of the therapeutic lens. Furthermore, a comparison of the therapeutic efficacy of the therapeutic lens has been done with topical administration and the drug uptake results from both the drug delivery modes have been validated with the experimental data reported in the literature. The developed model may help ophthalmologists to comprehend the transport and retention of different drugs in different domains and orientations of the human eye when administered through a therapeutic lens.